81.3k views
5 votes
Rewrite the polynomial-9x^5+36x^4+189x^3 in factored form, using the factoring method method you prefer.

User Sherb
by
5.4k points

2 Answers

3 votes

Answer:

The answer is -9x^3(x - 7) (x+3)

Rewrite the polynomial-9x^5+36x^4+189x^3 in factored form, using the factoring method-example-1
User Guille
by
5.2k points
3 votes

The polynomial 9x^5+36x^4+189x^3 in factored form is
-9 x * x * x *(x-7) *(x+3)

Solution:

Given, polynomial equation is
-9 x^(5)+36 x^(4)+189 x^(3)

We have to find the factored form of the above given polynomial equation.

Let us solve it by grouping.

Now, take the polynomial ⇒
-9 x^(5)+36 x^(4)+189 x^(3)

By taking common term out, we get


\rightarrow-9 x^(3)\left(x^(2)-4 x-21\right)


\rightarrow-9 x^(3)\left(x^(2)-(7-3) x-7 * 3\right)

Grouping the terms we get,


\rightarrow-9 x^(3)\left(\left(x^(2)-7 x\right)+(3 x-7 x^3)\right)

Taking common terms out from each group,


\rightarrow-9 x^(3)(x(x-7)+3(x-7))


\Rightarrow-9 x^(3)((x-7)(x+3))


\rightarrow-9 x * x * x *(x-7) *(x+3)

Thus the factored form of polynomial is found out

User Marc Pursals
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.